To the 65th birthday of Professor Vladimir Kirichenko (Algebra and Discrete Mathematics, 2007)
This is a special issue of the journal dedicated to the 65th birthday of an outstanding Ukrainian mathematician, one of the founders of our journal Professor Vladimir Kirichenko